2010
DOI: 10.1111/j.1743-6109.2010.01938.x
|View full text |Cite
|
Sign up to set email alerts
|

Flibanserin: Initial Evidence of Efficacy on Sexual Dysfunction, in Patients with Major Depressive Disorder

Abstract: Introduction Flibanserin, a novel 5-HT1A agonist and 5-HT2A antagonist, has the potential to treat sexual dysfunction. Aim Provide historical perspective on the rationale for development of flibanserin to treat sexual dysfunction, based on post hoc analyses of data. Main Outcome Measures The Arizona Sexual Experiences (ASEX) scale and the Hamilton depression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 29 publications
(32 reference statements)
1
35
0
Order By: Relevance
“…Tibolone has androgenic, estrogenic, and progesterone activity and it has been shown to improve desire, arousal, and lubrication. 95,103,107 Phentolamine is an a-antagonist that improves arousal and lubrication; 108 apomorphine, 94 a-melanocyte-stimulating hormones, 109 serotonin receptor antagonists, 110 and selective estrogen and androgen receptor modulators are in phase II trials. 112 Vasodilators as L-arginin, 112 alprostadile, 113 and herbal therapy (gingko biloba) 112 have an as yet undetermined role in the treatment of FSD.…”
Section: Therapeutic Approach To Sexual Dysfunction In Women With Diamentioning
confidence: 99%
“…Tibolone has androgenic, estrogenic, and progesterone activity and it has been shown to improve desire, arousal, and lubrication. 95,103,107 Phentolamine is an a-antagonist that improves arousal and lubrication; 108 apomorphine, 94 a-melanocyte-stimulating hormones, 109 serotonin receptor antagonists, 110 and selective estrogen and androgen receptor modulators are in phase II trials. 112 Vasodilators as L-arginin, 112 alprostadile, 113 and herbal therapy (gingko biloba) 112 have an as yet undetermined role in the treatment of FSD.…”
Section: Therapeutic Approach To Sexual Dysfunction In Women With Diamentioning
confidence: 99%
“…Flibanserin is a serotonin receptor subtype 1A (5HT1A) agonist and 2A (5HT2A) antagonist [1, 2] that has shown efficacy in treating female sexual interest/arousal disorder, formerly known as hypoactive sexual desire disorder [3, 4]. Although precise mechanisms of flibanserin effects on sexual behavior are still under study, flibanserin has been shown in rats to alter extracellular levels of dopamine and serotonin in the prefrontal cortex and nucleus accumbens in both male [5] and female rats [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…However the drug was found to improve the sexual health of the female participants in the study. 13 It was this initial observation that spurred on the impetus for developing the molecule in the treatment of hypoactive sexual desire disorder. The drug has also been studied in post-menopausal women and as shown improvement in sexual desire and it increase in the number of sexually satisfying events.…”
Section: Current Status and Future Directionsmentioning
confidence: 99%